A method for preparing a silicon-carbon negative electrode material for reducing interface side reactions

By using a specific ratio of passivating agent and gradient heat treatment technology in the silicon-carbon composite anode material, the SiO2/lithium silicate passivation layer is formed, which solves the interface side reaction problems of the silicon-carbon composite anode material during use, and significantly improves the material's cyclic performance and specific capacitance.

CN119674049BActive Publication Date: 2025-04-15ZHEJIANG GEYUAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510198931.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-15
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

There are interfacial side reaction problems during use of silicon-carbon composite anode material, resulting in volume expansion, loss of active material and sharp reduction in battery capacity.

Method used

A passivating agent formed in a specific proportion of ammonium carbonate and/or ammonium bicarbonate, aliphatic polybasic acid of C2-C8, and organic salts of lithium are used to form a uniform and dense SiO2/lithium silicate passivation layer on the porous carbon by gradient heat treatment to reduce interfacial side reactions.

Benefits of technology

Interface passivation of silicon-carbon negative electrode material is achieved, volume expansion is suppressed, interface side reactions are reduced, and the material's cyclic performance and specific capacitance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674049B_ABST
    Figure CN119674049B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a silicon-carbon negative electrode material for reducing interface side reactions, comprising the following steps: (S1) using an organic silicon source gas to perform chemical vapor deposition on porous carbon, so that amorphous silicon is attached to the pores of the porous carbon to obtain a silicon-carbon composite material; (S2) mixing a passivator with the silicon-carbon composite material and performing gradient heat treatment to obtain a silicon-carbon negative electrode material for reducing interface side reactions; the passivator is a compound of ammonium carbonate and / or ammonium bicarbonate, a C2-C8 aliphatic polyacid, and an organic salt of lithium in a mass ratio of 1: (1.5-3): (0.8-1.5). The components in the passivator of the present invention cooperate with each other to achieve partial passivation of the surface amorphous silicon in the porous carbon to form a uniform and dense passivation layer, and a small amount of carbon coating layer coated on the surface of the porous carbon is formed during the passivation process, thereby significantly reducing the interface side reactions of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a method for preparing a silicon-carbon negative electrode material capable of reducing interface side effects. Background Art

[0002] At present, the negative electrode material of lithium-ion batteries is mainly graphite, but the theoretical specific capacity of graphite negative electrode is low, while the theoretical specific capacity of silicon can reach 4200mAh / g, which is more than 10 times that of traditional graphite negative electrode materials. However, the volume expansion of silicon material itself during charging and discharging can be as high as 300%, which leads to the collapse of material structure and electrode peeling and powdering. Each time charging and discharging forms a new interface, silicon, lithium and electrolyte are continuously consumed, resulting in loss of active materials, sharp reduction of battery capacity and deterioration of cycle performance. Silicon-carbon composite negative electrode material is currently an effective means to solve the low specific capacity and alleviate the silicon expansion effect. For example, nano-silicon is filled in the porous carbon pores through the chemical vapor deposition silicon process, and then a layer of carbon is coated on the porous carbon outer layer of the deposited silicon to prepare a silicon-carbon composite negative electrode material. Silicon-carbon composite negative electrode material combines the advantages of silicon and carbon, and has high conductivity, good thermal stability and high specific capacity. This material has broad application prospects in lithium-ion batteries, solid-state batteries and other energy storage devices. However, silicon-carbon composite negative electrode materials have problems with interface side reactions during use, such as silicon has a large volume effect during the process of lithium insertion and extraction and it is difficult to form a stable SEI film; for example, silicon has poor compatibility with the electrolyte and will produce more side reactions with the electrolyte. In addition, the coated carbon layer is generally thin and is prone to cracking during long-term cyclic use, resulting in silicon exposure and failure to prevent the occurrence of interface side reactions; and in the process of carbon coating, since the deposited silicon is amorphous, it is easy to react with the carbon source to generate byproducts such as SiC, thereby reducing the first coulombic efficiency of the material. The above problems limit the further application and development of silicon-carbon negative electrode materials.

[0003] Related studies have shown that SiO 2 The chemical properties of the layer are stable, the expansion coefficient is small, and more stable lithium silicate can be formed in the process of forming the SEI film; in addition, SiO 2 The presence of the SiO layer can inhibit the formation of SiC during the carbon coating process, and at the same time isolate the internal amorphous silicon from the air to prevent further oxidation of silicon; that is, SiO 2 The silicon-carbon composite negative electrode material can be passivated by depositing silicon in the pores of porous carbon and then introducing CO 2 Gas or O 2 At a certain temperature, the silicon deposited on the shallow surface of the porous carbon is oxidized into silicon dioxide. 2 The existence of the layer inevitably reduces the initial efficiency of the silicon-carbon composite negative electrode material, so the oxidation process needs to be precisely controlled to form a uniform and dense SiO2 But directly through CO 2 The oxidation temperature is generally higher, reaching more than 350°C, which results in higher energy consumption and CO 2 The diffusion of O is uneven, the amount of oxidation is difficult to control, and it is difficult to obtain a uniform oxide layer. 2 The oxidation method is generally too fast, which can easily cause over-oxidation or uneven oxidation, and it is also difficult to form a dense and stable SiO 2 layer. Summary of the invention

[0004] In view of the problem that the silicon-carbon negative electrode material in the prior art has interface side reactions and cannot obtain a dense and stable passivation layer, the present invention provides a method for preparing a silicon-carbon negative electrode material with reduced interface side reactions. The prepared silicon-carbon negative electrode material has a uniform and dense SiO 2 / lithium silicate passivation layer, and the preparation process has low energy consumption.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a silicon-carbon negative electrode material for reducing interface side reactions comprises the following steps:

[0007] (S1) using an organic silicon source gas to perform chemical vapor deposition on porous carbon, so that part or all of the amorphous silicon is attached to the pores of the porous carbon, thereby obtaining a silicon-carbon composite material;

[0008] (S2) After mixing the passivator with the silicon-carbon composite material, the mixture is subjected to gradient heat treatment under an inert atmosphere to obtain a silicon-carbon negative electrode material with reduced interface side reactions; the passivator is a compound of ammonium carbonate and / or ammonium bicarbonate, a C2-C8 aliphatic polyacid, and an organic salt of lithium in a mass ratio of 1: (1.5-3): (0.8-1.5); the gradient heat treatment is: first, heat preservation at 200-250°C for 1-2h, then heat preservation at 300-350°C for 1-3h, and finally heat preservation at 400-600°C for 1-2h.

[0009] The inventors have found that the passivation agent formed by ammonium carbonate and / or ammonium bicarbonate, C2-C8 aliphatic polyacid, and lithium organic salt in a specific ratio can significantly reduce the interface side reaction of the material by gradient heat treatment of the silicon-carbon composite material formed by chemical vapor deposition silicon process. The possible reason is that the ammonium carbonate and / or ammonium bicarbonate in the passivation agent of the present invention decomposes at about 60°C to produce oxidizing gas CO 2 and H 2 O and NH 3 , CO 2 and H 2 O can oxidize the surface amorphous silicon, NH 3It has a corrosive effect on silicon and can promote the oxidation of amorphous silicon on the surface by oxidizing gases. The C2-C8 aliphatic polybasic acid in the passivator decomposes at about 150~200℃ and mainly produces oxidizing gas CO 2 and H 2 O; The organic salt of lithium in the passivator decomposes at about 200~300℃ and mainly produces oxidizing gas CO 2 and H 2 O and lithium oxide; that is, the passivating agent formed by the above three can slowly decompose in the whole temperature range of 60~300℃ to produce oxidizing gas CO 2 and H 2 O, these oxidizing gases can then react with the amorphous silicon deposited on the surface of the pores of the porous carbon to form SiO 2 layer, while lithium oxide can continue to bond with part of SiO 2 The reaction generates lithium silicate, that is, part of the amorphous silicon on the surface is passivated by the passivating agent to form SiO 2 / Lithium silicate passivation layer. SiO 2 The lithium silicate passivation layer plays an interface passivation role and has a lithium supplementation function, thereby achieving interface passivation of the silicon-carbon negative electrode material and inhibiting the volume expansion of the silicon-carbon negative electrode material, that is, reducing the interface side reaction. Since the temperature at which the passivator of the present invention decomposes to produce oxidizing gas is low, the surface passivation of amorphous silicon can be achieved at this temperature, and the oxidizing gas is produced by in-situ decomposition, so compared with directly introducing CO 2 and O 2 , the surface passivation method of the present invention is slower, and a more uniform and dense passivation layer can be obtained without excessive oxidation. The components of the passivator of the present invention cooperate with each other and work synergistically. The aliphatic polyacid of C2-C8 mainly plays a passivation role. If the content is too low, the passivation effect is limited, and if the content is too high, it is easy to cause excessive oxidation of amorphous silicon; ammonium carbonate and / or ammonium bicarbonate promote passivation. If the content is too low, the promotion of passivation is limited, and if the content is too high, the density of the passivation layer will be reduced; organic salts of lithium play a synergistic role in passivation and lithium supplementation; the three can only be achieved in a specific ratio range to achieve slow decomposition in the entire temperature range of 60~300℃ to produce oxidizing gas and obtain a uniform and dense passivation layer.

[0010] On the other hand, the C2-C8 aliphatic polyacid in the passivator is also a high-content carbon source, which can carbon-coat the silicon-carbon composite material under subsequent high-temperature heat treatment; at the same time, since a uniform and dense passivation layer has been formed in the passivation stage, the carbon coating layer produced in this stage can meet the use requirements of the silicon-carbon negative electrode material, and no additional gas-phase carbon source needs to be added for carbon coating, that is, a relatively small amount of carbon coating layer can meet the use requirements. The silicon content of the silicon-carbon negative electrode material finally formed is relatively higher, which is more advantageous than the capacitance.

[0011] The components of the above passivating agent cooperate with each other to partially passivate the surface amorphous silicon in the porous carbon to form a uniform and dense passivation layer, and to form a small amount of carbon coating layer on the surface of the porous carbon during the passivation process. The proportions of the components in the passivating agent must be strictly controlled to achieve the above effect.

[0012] Furthermore, in step (S1), the median particle size D50 of the porous carbon is 3-10 μm, and the pore volume is 0.8-1.2 cm 3 / g, specific surface area is 1500~2200m 2 / g, the average pore size is 1.1-2nm, and the proportion of micropores is more than 95%, preferably more than 98%.

[0013] Furthermore, in step (S1), the organic silicon source gas is selected from at least one of monosilane, disilane, dichlorosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

[0014] Furthermore, in step (S1), the usage ratio of the porous carbon to the organosilicon source gas is 1 kg: (500-900) L; the chemical vapor deposition conditions are: deposition for 3 h to 6 h under an inert atmosphere at 450° C. to 600° C., and the inert atmosphere is nitrogen and / or argon and / or helium.

[0015] Furthermore, in step (S2), the amount of the passivating agent used is 5-15wt%, preferably 8-12wt% of the porous carbon.

[0016] Preferably, in step (S2), the passivating agent is a compound of ammonia carbonate, C2-C8 aliphatic polyacid, and lithium organic salt in a mass ratio of 1: (2-2.5): (1-1.2).

[0017] Furthermore, in step (S2), the C2-C8 aliphatic polyacid is at least one of oxalic acid, tartaric acid, malic acid, and citric acid, preferably citric acid; the organic salt of lithium is at least one of lithium acetate, lithium oxalate, lithium phenolate, and lithium ethoxide, preferably lithium oxalate or lithium ethoxide.

[0018] In step (S2), the inert atmosphere is nitrogen and / or argon and / or helium.

[0019] In a second aspect, the present invention further provides a silicon-carbon negative electrode material for reducing interfacial reactions, which is prepared by the aforementioned preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The passivating agent formed by compounding ammonium carbonate and / or ammonium bicarbonate, C2-C8 aliphatic polyacid, and lithium organic salt in a specific ratio in the present invention can slowly decompose and produce CO in the entire temperature range of 60-300°C. 2 , H 2 O and other oxidizing gases and lithium oxides can slowly passivate the amorphous silicon deposited in the pores of porous carbon to form a uniform and dense SiO 2 / lithium silicate passivation layer; at the same time, since the temperature of the decomposition of the passivator to produce oxidizing gas is lower, and the oxidizing gas is produced by in-situ decomposition, it is more efficient than directly introducing CO 2 and O 2 , the surface passivation method of the present invention will not be over-oxidized. That is, the passivator and passivation method of the present invention realize the interface passivation of the silicon-carbon negative electrode material and inhibit the volume expansion of the silicon-carbon negative electrode material, thereby significantly reducing the interface side reaction of the material.

[0022] (2) The present invention adopts gradient heat treatment to ensure that a dense and uniform passivation layer is formed in the passivation stage. In the subsequent high-temperature heat treatment stage, the C2-C8 aliphatic polyacid in the passivator is also a carbon source, thereby realizing carbon coating of the silicon-carbon composite material. At the same time, since a uniform and dense passivation layer has been formed in the passivation stage, there is no need to add an additional gas-phase carbon source for carbon coating, that is, a relatively small amount of carbon coating layer can meet the use requirements; the silicon-carbon negative electrode material finally formed has a relatively higher silicon content, which is more advantageous than the capacitance.

[0023] (3) The preparation process of the present invention is simple and easy to control, with relatively low energy consumption, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD pattern of the silicon-carbon negative electrode material prepared in Example 1;

[0025] Figure 2 This is a SEM image of the silicon-carbon negative electrode material prepared in Example 1;

[0026] Figure 3 TEM and element distribution diagram of the silicon-carbon negative electrode material prepared in Example 1;

[0027] Figure 4 This is the XPS spectrum of the silicon-carbon negative electrode material prepared in Example 1;

[0028] Figure 5 This is the first charge and discharge curve of a lithium battery assembled with the silicon-carbon negative electrode material prepared in Example 1 at a rate of 0.1C. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0030] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0031] The porous carbon was homemade, with a median particle size D50 of 7.6 μm and a pore volume of 0.85 cm 3 / g, average pore size is 1.8nm, micropores account for 97.1%, and specific surface area is 1840m 2 / g.

[0032] Example 1

[0033] (S1) 1 kg of porous carbon is placed in a rotary kiln with a rotation speed of 20 rpm, and nitrogen is introduced at a flow rate of 6 L / min. After the temperature is raised to 500°C in a nitrogen environment, the nitrogen flow rate is maintained and monosilane gas is introduced at a flow rate of 2.3 L / min for chemical vapor deposition for 6 hours. Under the adsorption effect of the porous carbon, silane is adsorbed in its pores and cracked to obtain a silicon-carbon composite material. After the monosilane deposition is completed, the monosilane gas is stopped, and nitrogen is continuously introduced at a flow rate of 6 L / min to remove excess monosilane gas, and then cooled to room temperature;

[0034] (S2) Ammonium carbonate, malic acid and lithium acetate are compounded in a mass ratio of 1:1.5:0.8 to form 50 g of a passivating agent, which is then placed in a rotary kiln containing the above-mentioned silicon-carbon composite material, and nitrogen is introduced at a flow rate of 1 L / min. The temperature is raised to 250°C in a nitrogen environment and kept warm for 1 hour, then raised to 350°C and kept warm for 1 hour, and finally raised to 600°C and kept warm for 1 hour. The mixture is naturally cooled to room temperature to obtain a silicon-carbon negative electrode material with reduced interfacial side reactions.

[0035] Example 2

[0036] The rest is the same as Example 1, except that in step (S2), the mass ratio of ammonium carbonate, malic acid and lithium acetate is 1:2:1.

[0037] Example 3

[0038] The rest is the same as Example 1, except that in step (S2), the mass ratio of ammonium carbonate, malic acid and lithium acetate is 1:2.5:1.2.

[0039] Example 4

[0040] The rest is the same as Example 1, except that in step (S2), the mass ratio of ammonium carbonate, malic acid and lithium acetate is 1:3:1.5.

[0041] Example 5

[0042] The rest is the same as Example 3, except that: in step (S2), citric acid is used instead of malic acid, lithium oxalate is used instead of lithium acetate, and the gradient heat treatment is specifically: 200°C for 2h, 300°C for 3h, and 400°C for 2h.

[0043] Example 6

[0044] The rest is the same as Example 1, except that the amount of the passivating agent used in step (S2) is 80 g.

[0045] Example 7

[0046] The rest is the same as Example 1, except that the amount of the passivating agent used in step (S2) is 120 g.

[0047] Example 8

[0048] The rest is the same as Example 1, except that the amount of the passivating agent used in step (S2) is 150 g.

[0049] Comparative Example 1

[0050] The rest is the same as Example 1, except that: in step (S2), the passivating agent is a compound of ammonium carbonate and lithium acetate in a mass ratio of 1:0.8, that is, malic acid is not added.

[0051] Comparative Example 2

[0052] The rest is the same as Example 1, except that: in step (S2), the passivating agent is ammonium carbonate and malic acid compounded in a mass ratio of 1:1.5, that is, no organic salt of lithium is added.

[0053] Comparative Example 3

[0054] The rest is the same as Example 1, except that: in step (S2), the passivating agent is ammonium carbonate, terephthalic acid, and lithium acetate compounded in a mass ratio of 1:1.5:0.8, that is, terephthalic acid is used instead of malic acid.

[0055] Comparative Example 4

[0056] The rest is the same as Example 1, except that in step (S2), the heat treatment is a constant temperature treatment, that is, no gradient heat treatment is performed, and the specific process is: ammonium carbonate, malic acid, and lithium acetate are compounded in a mass ratio of 1:1.5:0.8 to form 50g of a passivating agent, which is then placed in a rotary kiln containing the above-mentioned silicon-carbon composite material, and nitrogen is introduced at a flow rate of 1L / min. The temperature is raised to 250°C in a nitrogen environment, and then kept warm for 3h, and naturally cooled to room temperature to obtain a silicon-carbon negative electrode material with reduced interface side reactions.

[0057] A mixed gas of nitrogen and oxygen (of which the oxygen accounts for 5 vol%) is introduced into the rotary kiln containing the silicon-carbon composite material at a flow rate of 0.1 L / min. The temperature is kept constant at 25°C to ensure that the material is slowly passivated and does not catch fire.

[0058] Testing and analysis

[0059] 1) Test of structure, performance and element content of silicon-carbon negative electrode materials

[0060] In accordance with GB / T 38823-2020, XRD, XPS, SEM and TEM were used to analyze the phase, elements, morphology and structure of the silicon-carbon negative electrode materials prepared in the embodiments and comparative examples. Figure 1 The XRD pattern of the silicon-carbon negative electrode material obtained in Example 1 is shown in FIG. Figure 1 It can be seen that the silicon-carbon negative electrode material prepared in Example 1 is o There is a diffuse peak nearby, indicating that silicon mainly exists in amorphous form; and the peak shape and position have not changed, indicating that the passivation of the shallow layer does not affect the phase composition of the overall material. Figure 2 This is the SEM image of the silicon-carbon negative electrode material obtained in Example 1. Figure 2 It can be seen that the surface is smooth and there are no obvious particles, indicating that silicon is basically deposited inside the porous carbon. Figure 3 TEM and element distribution diagram of the silicon-carbon negative electrode material prepared in Example 1. Figure 3 It can be seen that silicon and oxygen elements are evenly distributed, indicating that the formed passivation layer is uniform and dense. Figure 4 This is the XPS spectrum of the silicon-carbon negative electrode material prepared in Example 1, Figure 4 The three elements Si, C, and O were detected (Li element could not be detected by XPS because it was too light), indicating that the passivation method of the present invention did not introduce other impurities.

[0061] According to GB / T 38823-2020, the German Elementar company vario EL cube The element analyzer is used to test the silicon content in the silicon-carbon negative electrode material, and the HCS-801 infrared carbon-sulfur analyzer is used to test the carbon content in the silicon-carbon negative electrode material; the oxygen, nitrogen and hydrogen analyzer is used to test the oxygen content in the silicon-carbon negative electrode material. By measuring the content of silicon, oxygen and carbon in the prepared silicon-carbon negative electrode material, the amorphous silicon and passivation layer SiO in the silicon-carbon negative material can be calculated. 2 / The mass proportion of lithium silicate and carbon, and the carbon comes from the carbon coating formed by the raw porous carbon and the carbon source in the passivator, and then the respective proportions of the porous carbon and the carbon coating can be calculated by the incremental method. After calculation, it is found that the amorphous silicon in the silicon-carbon negative electrode material prepared in the embodiment of the present invention accounts for 48-50wt% of the silicon-carbon negative electrode material, the passivation layer accounts for 0.6-1.5wt% of the silicon-carbon negative electrode material, and the carbon coating accounts for 0.9-1.8wt% of the silicon-carbon negative electrode material.

[0062] 2) Electrochemical performance test

[0063] Gas production test: 5 g of the silicon-carbon negative electrode material prepared in the embodiment or comparative example was placed in a mixture of 0.76 g of ethanol and 7.5 g of deionized water, stirred evenly, transferred to an aluminum-plastic bag, and vacuum-sealed. The initial slurry density was measured using a solid density meter and recorded as ρ 0 ; Store in a water bath at 35°C for 7 days and test the density again, recorded as ρ 1 ; Gas production = , where m is the mass of the slurry. The more gas produced, the worse the interface stability of the material.

[0064] Charge and discharge test: The silicon-carbon negative electrode material prepared in the embodiment and the comparative example is applied to the negative electrode of the lithium-ion battery, assembled into a lithium-ion button half-cell, and its electrochemical performance is tested. The specific steps are: the prepared silicon-carbon negative electrode material, conductive carbon black Super P and polyacrylonitrile binder LA133 are mixed in a mass ratio of 91:3:6 to form a slurry (wherein the solid content of the polyacrylonitrile binder LA133 is 5%), the slurry is evenly applied to the copper foil current collector, and vacuum dried at 80°C for 12 hours to form a negative electrode sheet; the counter electrode is a metal lithium sheet, the diaphragm is Celgard2400, the electrolyte is 1 mol / LLiPF6 solution (wherein the solvent is prepared in a volume ratio of ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) = 1:1:1), and the button cells are assembled in a glove box with an argon atmosphere. The above assembled battery was subjected to charge and discharge tests on a LAND battery tester, with a voltage range of 0.01V~1.5V and a current density of 1C (1C=1800mAh / g).

[0065] Figure 5 The first charge and discharge curve of a lithium battery assembled with the prepared silicon-carbon negative electrode material at a rate of 0.1C.

[0066] The gas production test and charge and discharge results are shown in Table 1.

[0067] Table 1 Performance test

[0068] .

[0069] As can be seen from Table 1, the silicon-carbon negative electrode material prepared in the embodiment of the present invention has good stability in water, and its gas production at 35°C for 7 days is less than 0.4 ml / g, indicating that the silicon-carbon negative electrode material prepared after passivation treatment of the present invention has less interfacial side reactions, that is, without adding additional gas-phase carbon source for carbon coating, the passivation layer formed by the present invention can effectively isolate external water and oxygen. At the same time, when the silicon-carbon negative electrode material prepared in the embodiment is used as the negative electrode of a lithium battery, its first discharge specific capacity is as high as 1700 mAh / g or more, the first coulomb efficiency is more than 91%, and the capacity retention rate after 100 cycles is more than 90%.

[0070] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material for reducing interface side reactions, characterized in that: The following steps are involved: (S1) using an organic silicon source gas to perform chemical vapor deposition on porous carbon, so that amorphous silicon is attached to the pores of the porous carbon to obtain a silicon-carbon composite material; (S2) After mixing the passivator with the silicon-carbon composite material, the mixture is subjected to gradient heat treatment under an inert atmosphere to obtain a silicon-carbon negative electrode material with reduced interface side reactions; the passivator is a compound of ammonium carbonate and / or ammonium bicarbonate, a C2-C8 aliphatic polyacid, and an organic salt of lithium in a mass ratio of 1: (1.5-3): (0.8-1.5); the gradient heat treatment is: first, heat preservation at 200-250°C for 1-2h, then heat preservation at 300-350°C for 1-3h, and finally heat preservation at 400-600°C for 1-2h.

2. The preparation method according to claim 1, characterized in that: In step (S1), the median particle size D50 of the porous carbon is 3-10 μm, and the pore volume is 0.8-1.2 cm 3 / g, specific surface area is 1500~2200m 2 / g, the average pore size is 1.1~2nm, and the proportion of micropores is more than 95%.

3. The preparation method according to claim 1, characterized in that: In step (S1), the organic silicon source gas is selected from at least one of monosilane, disilane, dichlorosilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride.

4. The preparation method according to claim 1, characterized in that: In step (S1), the usage ratio of the porous carbon to the organosilicon source gas is 1 kg: (500-900) L; the chemical vapor deposition conditions are: deposition for 3 h to 6 h in an inert atmosphere at 450°C to 600°C, wherein the inert atmosphere is nitrogen and / or argon and / or helium.

5. The preparation method according to claim 1, characterized in that: In step (S2), the amount of the passivating agent used is 5-15wt% of the porous carbon.

6. The preparation method according to claim 1, characterized in that: In step (S2), the amount of the passivating agent used is 8-12 wt % of the porous carbon.

7. The preparation method according to claim 1, characterized in that: In step (S2), the passivating agent is a mixture of ammonia carbonate, C2-C8 aliphatic polyacid, and lithium organic salt in a mass ratio of 1: (2-2.5): (1-1.2).

8. The preparation method according to claim 1, characterized in that: In step (S2), the C2-C8 aliphatic polyacid is at least one of oxalic acid, tartaric acid, malic acid, and citric acid; and the organic salt of lithium is at least one of lithium acetate, lithium oxalate, lithium phenolate, and lithium ethoxide.

9. The preparation method according to claim 1, characterized in that: In step (S2), the C2-C8 aliphatic polyacid is citric acid; and the organic salt of lithium is lithium oxalate or lithium ethoxide.

10. A silicon-carbon negative electrode material for reducing interfacial reaction, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery pre-lithiated silicon-carbon multilayer composite negative electrode material and preparation method thereof

    CN110620223A

  • Negative electrode material as well as negative electrode plate and battery comprising negative electrode material

    CN114864909A